From Digitization to the AI Era: Digital Technology Trajectories in Fine-Art Creation - Yang, Hu; Zou, Yu; Gao, Bo (Asia Pacific Economic and Management Review, 2026)
This article analyzes how digital technologies have reconfigured fine-art creation from early computer graphics to contemporary generative AI. It advances a practice-centered periodization that links changing tool affordances to shifts in authorship, originality, distribution, and the political economy of creative labor. Three phases are identified: medium translation (1980–2000), when images became file-based and procedural logics entered artistic craft; platformized networking (2000–2010), when Web 2.0 expanded participation while structuring visibility through interfaces, metrics, and attention regimes; and algorithmic autonomy (2010–present), when GANs and diffusion models made style and composition statistically learnable and widely replicable. The AI phase intensifies long-standing debates by redistributing artistic agency across prompts, model priors, datasets, and post-selection, while deepening dependence on data extraction and platform governance. In response, the article proposes technological humanism as a normative-analytic framework for AI-mediated art: it centers traceable delegation, situated cultural responsibility, and infrastructural transparency as conditions of accountable creation. The paper concludes with operational principles for artists, educators, and museums to evaluate and sustain agency and cultural integrity under algorithmic production.